The Bad Guys - Blabey, Aaron (New York, NY Scholastic Inc, 2017)
The Bad Guys, Mr. Wolf, Mr. Shark, Mr. Snake, and Mr. Piranha, want to be heroes, and they decide that the way to do it is free the 200 dogs in the city dog pound--but their plan soon goes awry
"First published by Scholastic Australia Pty Limited in 2015."
English stories
Keywords: Animals -- Juvenile fiction; Heroes -- Juvenile fiction; Rescues -- Juvenile fiction; Animals -- Fiction; Heroes -- Fiction; Humorous stories; Rescues -- Fiction